2010
DOI: 10.1007/s00280-010-1284-2
|View full text |Cite
|
Sign up to set email alerts
|

Biweekly vinorelbine and gemcitabine as second-line and beyond treatment in ovarian cancer

Abstract: The vinorelbine plus gemcitabine combination at the present doses and schedule is a safe but ineffective regimen, and therefore, is not recommended as second-line and beyond treatment in patients with refractory ovarian cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Mild neurotoxicity was observed in 5 patients and among them only 1(2.9%) was experiencing G2. By analysis other studies of OXL and VNR it is seen that toxicity profile is better and similar with most of the studies (4,27,(37)(38)(39)(40) and can be manageable with conservative treatments.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Mild neurotoxicity was observed in 5 patients and among them only 1(2.9%) was experiencing G2. By analysis other studies of OXL and VNR it is seen that toxicity profile is better and similar with most of the studies (4,27,(37)(38)(39)(40) and can be manageable with conservative treatments.…”
Section: Discussionsupporting
confidence: 55%
“…4,38 VNR (30mg/m 2 ) with Gemcitabine combination showed an ORR of 11% and SD of 24%, PD 65%. 39 However, OXL (100 mg/m 2 ) with Gemcitabine had the ORR of 37% and SD of 41%. 40 The median DFS of this regimen was 17.05 months (95% CI, -29.1 to 55.2) with an optimum of 21.3 months after a median follow up of 3.1 months.…”
Section: Discussionmentioning
confidence: 96%
“…For example, Ferrero et al described a response rate of 49% with gemcitabine and vinorelbine in platinum-sensitive patients [5], whereas Burger et al found a response rate of 29% in a mixed resistant-sensitive population [6]. Lower response rates are seen among platinum-resistant patients with response rates of 25% [7], 21% [8], 11% [9], and even 3% [10] with doxorubicin and gemcitabine, topotecan and oxaliplatin, gemcitabine and vinorelbine, and vinorelbine in various combinations and dosages, respectively. Regarding survival, palliative chemotherapy regimens achieve median overall survival rates after the first, second, third, fourth, and fifth relapse of 17.6 (95% CI 16.4–18.6), 11.3 (10.4–12.9), 8.9 (7.8–9.9), 6.2 (5.1–7.7) and 5.0 (3.8–10.4) months, respectively [11].…”
Section: Introductionmentioning
confidence: 99%